THE CHALLENGES OF TEACHER EDUCATION IN THE 21ST CENTURY NIGERIA - Cherechi, Israel Happiness (PEOPLE: International Journal of Social Sciences, 2018)
Education is universally viewed as the vehicle that is capable of importing and exporting transformational behavior, growth and sustainability of nation’s wealth. It is a channel to articulate new ideas, thought and futuristic aspirations of an individual and nation at large. Nigeria has witnessed several educational reforms as evidenced in the number of revisions of her National Policy on Education. . However ,with the growing trend of the global education which entails the use of Science/Technology and Information Communication Technology (ICT) and where the communication infrastructure like telephone, fax, e-mail and computer networking have turned the world into a global village, Nigeria Teacher Education has been placed at a disadvantaged position. This paper therefore adopted the use of historical approach to argue out the contentious issues involved. It further observed with dismay that inconsistencies in government policy formulation and haphazard implementation of such policies have sufficiently affected the quality of education delivery in Nigeria. It therefore suggests that the regulatory bodies or agencies responsible for the training of Teachers in Nigeria should embark on aggressive reforms in order to re-direct Teacher Education in Nigeria to meet global expectations. It finally submits that since education is the only valuable asset a nation can offer to her citizens, politics should not be brought to bear on anything that has to do with it in order to avoid a situation whereby, the future of the citizens is jeopardized educationally.